High‐Temperature Stable Zirconia Particles Doped with Yttrium, Lanthanum, and Gadolinium. (13th June 2016) - Leib, Elisabeth W.; Pasquarelli, Robert M.; Blankenburg, Malte; Müller, Martin; Schreyer, Andreas; Janssen, Rolf; Weller, Horst; Vossmeyer, Tobias
Abstract : Zirconia microspheres synthesized by a wet‐chemical sol–gel process are promising building blocks for various photonic applications considered for heat management and energy systems, including highly efficient reflective thermal barrier coatings and absorbers/emitters used in thermophotovoltaic systems. As previously shown, pure zirconia microparticles deteriorate at working temperatures of ≥1000 °C. While the addition of yttrium as a dopant has been shown to improve their phase stability, pronounced grain growth at temperatures of ≥1000 °C compromises the photonic structure of the assembled microspheres. Here, a new approach for the fabrication of highly stable ceramic microparticles by doping with lanthanum, gadolinium, and a combination of those with yttrium is introduced. The morphological changes of the particles are monitored by scanning electron microscopy, ex situ X‐ray diffraction (XRD), and in situ high‐energy XRD as a function of dopant concentration up to 1500 °C. While the addition of lanthanum or gadolinium has a strong grain growth attenuating effect, it alone is insufficient to avoid a destructive tetragonal‐to‐monoclinic phase transformation occurring after heating to >850 °C. However, combining lanthanum or gadolinium with yttrium leads to particles with both efficient phase stabilization and attenuated grain growth. Thus, ceramic microspheres are yielded that remain extremely stable after heating to 1200 °C. Abstract : Zirconia microspheres doped with lanthanum, gadolinium, and yttrium are synthesized via a sol–gel procedure . Through an analysis of their morphology, crystalline phases, and grain growth behavior by means of SEM and XRD after heating up to 1500 °C, it is shown that they exhibit superior thermal stability in comparison to previously synthesized pure or yttrium‐monodoped particles.